The anti-infective potential of human milk oligosaccharides in carbohydrate powder in implant-associated infection with Staphylococcus aureus - Julian Koettnitz; Franz Koettnitz; Tobias Tiemann; Gael Vos; Kevin Pagel; Silke Zechel-Gran; Eugen Domann (PLoS ONE, 2026)
Introduction Periprosthetic joint and implant-associated infections remain serious complications despite highly standardized diagnostic and therapeutic protocols. Repeated revision procedures substantially increase morbidity and the risk of therapeutically uncontrollable infection scenarios. This pilot study, we evaluated the effect of HMO (human milk oligosaccharides)-containing carbohydrates on S. aureus biofilm formation using crystal violet assays and implant models. Methods S. aureus EDCC 5055 biofilm formation was quantified in the presence of HMO-containing carbohydrates (HMO-C) at concentrations of 5%, 7%, 9%, and 11% and lactose-alone in 96-well plates. After processing, the plate contents were read out using a 595nm Phomo plate reader (Anthos Mikrosystems, Krefeld, Germany). Biofilm activity was further evaluated on titanium disks pre-incubated with HMO-C solutions. Bacterial growth kinetics were also analyzed in TSB with the 5% to 11% HMO-C solutions. Results The results demonstrated a significant reduction in S. aureus biofilm formation with the addition of HMO-C (HMO-C-5%: mean value ( x¯ )=0.271nm; p = 0.021; HMO-C groups 7%−11%: x¯ = 0.211nm, 0.179nm, 0.147nm; All p = 0.001) against the positive control EDCC 5055 (PC) ( x¯ = 0.335nm). Lactose (L) alone did not significantly affect biofilm formation (L5%−11%: p = 1.0). No significant biofilm reduction was observed for titanium implants, though medium changes indicated bacterial inhibition at higher HMO-C solutions (9%−11%: x¯ = 0.844nm, 0.940nm; Both p = 0.001). Conclusion Media supplemented with HMOS-C significantly reduced S. aureus ED CC 5055 biofilm formation in vitro in the crystal violet microtiter plate assay. Bacterial invasion on titanium could not be demonstrably changed, but S. aureus growth curve was significantly reduced. Further studies with optimized implant models and standardized HMO formulations are warranted to clarify the translational potential of HMO-C for the prevention of implant-associated infections.